University teachers' use of motivational strategies in second language classes - Hajan, Bonjovi H.; Castillo, Brenfel D.; Tendero, Julieta B. (2014)
This study aimed to determine any significant difference in the frequency of use of motivational strategies among 42 respondents randomly selected from the population of 54 second languages teachers coming from two colleges and one department at the Western Mindanao State University with consideration of the variables of course finished, length of service and educational attainment. To pursue with its objectives, the study made use of the descriptive-quantitative research method using t-test for independent samples and ANOVA as the main statistical tools for analysis. Main findings showed that there was a significant difference in the respondents' frequency of use of motivational strategies when data were grouped by length of service and educational attainment (p<0.05). It is recommended, then, that the utilization of motivational strategies in second language classes at the university context be maintained or used always while those that were used only sometimes be more maximized and realized, especially that the university in its continuing academic endeavors has been aiming for the Center of Excellence. Hence, the language departments may be encouraged to include the use of these motivational strategies in their orientation for teachers who are new or young in the teaching profession. For future researchers, the study recommends the conduct of similar research with the inclusion of teachers coming from other schools in the region for a wider scope of study and students as respondents to validate teachers' use of these motivational strategies.
Keywords: Education; Motivational strategies; Second language teachers; Mindanao studies